Pengaruh Tinggi Tapak Timbun Terhadap Distribusi Akar Kelapa Sawit (Elaeis guineensis Jacq.) Umur 10 Tahun Pada Lahan Mineral - Nursiani Lubis; Muhammad Amrul Khoiri; Riko Irawan (Jurnal Agrotek Lestari, 2023)
One of the reasons for the low productivity of oil palm is the lack of proper technical culture implementation. The implementation of technical culture practices that can be carried out includes stem mounding by creating mound platforms for the oil palm. This study aims to determine the effect of mound bed height on the growth and development of roots in 10-year-old oil palm plants. The research was conducted experimentally using a Non-Factorial Randomized Complete Block Design with 5 levels of mound bed height: 20 cm, 25 cm, 30 cm, 35 cm, and 40 cm. Each treatment was replicated five times, resulting in 25 experimental units. Each experimental unit consisted of three sample plants, making a total of 75 sample plants. The observed parameters included fresh root weight, dry root weight, the number of primary roots, the length of primary roots, the number of secondary roots, the length of secondary roots, and the number of tertiary roots. The results of the study indicated that the mound bed treatment on 10-year-old oil palm plants in mineral soil, particularly at a height of 40 cm, tended to increase the fresh root weight by 2.45 g, the dry root weight by 0.65 g, the number of tertiary roots by 5.26 strands, the number of primary roots by 2.80 strands, the length of primary roots by 10.0 cm, the number of secondary roots by 2.26 strands, and the length of secondary roots by 2.61 cm.